2009
DOI: 10.1007/s10803-009-0746-z
|View full text |Cite
|
Sign up to set email alerts
|

The Autism Diagnostic Observation Schedule—Toddler Module: A New Module of a Standardized Diagnostic Measure for Autism Spectrum Disorders

Abstract: The Autism Diagnostic Observation Schedule (ADOS; Lord et al., 2000) is widely accepted as a "gold standard" diagnostic instrument, but it is of restricted utility with very young children. The purpose of the current project was to modify the ADOS for use in children under 30 months of age. A modified ADOS, the ADOS Toddler Module (or Module T), was used in 360 evaluations. Participants included 182 children with best estimate diagnoses of ASD, non-spectrum developmental delay or typical development. A final s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
337
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 397 publications
(353 citation statements)
references
References 32 publications
(37 reference statements)
10
337
1
5
Order By: Relevance
“…The development paper 76 involved 182 children with best estimate diagnoses of ASD, non-spectrum developmental delay or typical development, aged 12-30 months. Content validity was good; items were revised, rewritten or removed, as necessary, until all remaining items were deemed relevant.…”
Section: Autism Diagnostic Observation Schedule-toddler Modulementioning
confidence: 99%
See 2 more Smart Citations
“…The development paper 76 involved 182 children with best estimate diagnoses of ASD, non-spectrum developmental delay or typical development, aged 12-30 months. Content validity was good; items were revised, rewritten or removed, as necessary, until all remaining items were deemed relevant.…”
Section: Autism Diagnostic Observation Schedule-toddler Modulementioning
confidence: 99%
“…70 The ADOS-G was able to measure improvement in functioning over time in Ben Itzchak et al 149 and change scores for ADOS-G and ADI-R gave similar findings in Lord et al 65 Autism Diagnostic Observation Schedule-Toddler Module but the paper 76 was judged to be of poor quality for this property, as the measurement was for the agreement of seven raters and 14 videos of assessment. Luyster et al 76 also reported that numerous drafts and pilot analyses for content validity were conducted, and items removed and added as appropriate.…”
Section: Autism Diagnostic Observation Schedule-genericmentioning
confidence: 99%
See 1 more Smart Citation
“…Experienced diagnosticians administered the Autism Diagnostic Observation Schedule (ADOS), [38][39][40] home observation, parent report measures, standardized measures, and developmental history. Clinical judgment was used to make a best estimate diagnosis, the gold standard 41,42 shown to predict later diagnosis.…”
Section: Participantsmentioning
confidence: 99%
“…Participants received Module 1, 2, 3, or the Toddler Module (Luyster et al, 2009) on the basis of age and expressive language level. Diagnostic classifications of "nonspectrum" or "ASD" were based upon the overall total score.…”
Section: Adosmentioning
confidence: 99%